The Relevance of Prophetic Hadith on Knowledge in Modern Islamic Education: Exploring the Role of Digitalization and Motivation in Learning - Indriani Safitri; Izzatinur Fathiyah; Nabila Athia Ning Tyas (Aqwal: Journal of Qur'an and Hadis Studies, 2025)
Background and Objectives: Education in Indonesia faces significant challenges, as reflected in its low global rankings in education quality. One of the primary factors contributing to this issue is the lack of student motivation, often driven by boredom and a lack of understanding of the material. This study aims to explore the relevance of a hadith from Prophet Muhammad (SAW) about the virtue of those who acquire and teach knowledge, and contextualize this hadith within modern Islamic education, especially in the face of digitalization. Methodology: This qualitative research employs a library research method, utilizing primary data from the books Syarh Ibnu Baththal and Al-Minhaj Syarh Shahih Muslim. Secondary data is gathered from relevant literature on Islamic education and technology. The data is analyzed using linguistic studies and hadith authentication (takhrij). Main Results: The study reveals that the hadith likening knowledge to beneficial rain highlights the importance of spreading knowledge. It categorizes people into three types based on how they receive knowledge: those who absorb and teach it, those who lack understanding, and those who reject it. In the digital age, the ability to receive and apply knowledge depends heavily on individual readiness and technology. Contributions: This research contributes by linking classical Islamic teachings with contemporary educational challenges, especially digitalization. It enriches the understanding of how Islamic education principles can be applied in the modern context, integrating technology with moral and academic development. Conclusions: The hadith about knowledge remains a timeless guide in Islamic education. Education today should focus on integrating knowledge, ethics, and technology to shape individuals who are not only intellectually competent but also morally grounded, prepared to face global challenges.